P2 Incorporation of an in-depth thoracic ultrasound assessment into routine pre-procedural evaluation of patients with pleural effusions. (15th November 2016) - Corcoran, JP; Talwar, A; Hallifax, RJ; Psallidas, I; Wrightson, JM; Rahman, NM
Abstract : Background: Pleural disease affects 1 in 300 people annually; furthermore, the incidence of malignant pleural effusion (MPE) is increasing with over 40, 000 cases each year in the UK alone. A significant minority of patients will have non-expandable lung (NEL) secondary to underlying disease. At present, there is no way of pre-emptively identifying these individuals; with current strategies such as pleural manometry requiring invasive intervention. Early recognition of patients with NEL would streamline care and allow them to be offered appropriate treatment; i.e., indwelling pleural catheter insertion rather than chemical pleurodesis. Recent research 1 has described the novel use of thoracic ultrasound (TUS) to identify NEL by assessing mobility and compliance of the atelectatic lung within an effusion. However, this work has not been replicated and was delivered by researchers with expertise and facilities not used by or available to most practitioners. Method: We incorporated an in-depth TUS protocol into the pre-procedural assessment of patients undergoing intervention for suspected MPE, where ≥500 mL of fluid was expected to be drained. TUS images were acquired by two chest physicians with RCR level 1 competence or above. Data recorded included size and characteristics of the effusion; presence of pleural thickening; behaviour of the lung and diaphragm; and M-mode displacement with cardiac impulse of the atelectatic lung during breath hold manoeuvres. NEL was determined using post-drainage imaging (chest X-ray and/or CT) and clinical notes. Results: 34 patients underwent in-depth TUS evaluation (Table 1 ). Image acquisition and measurements took no more than five minutes in any patient. Poor M-mode displacement (<0.8 mm) was only seen with NEL, whilst good movement (>1.2 mm) was highly predictive of free lung. The presence of visceral thickening on TUS may also predict NEL, although there was only limited data to support this finding. Conclusion: In-depth TUS assessment can be delivered and interpreted quickly in the day-case setting using widely available portable ultrasound equipment, with potential implications for patient care and non-invasive diagnosis of NEL. Further research is needed to evaluate the ability of M-mode and other TUS parameters to predict NEL and symptom response prior to invasive intervention. Reference: Salamonsen MR, et al . Novel use of pleural ultrasound can identify malignant entrapped lung prior to effusion drainage. Chest 2014;146 (5):1286–93.